[18F]‐NOTA‐FAPI‐04 PET/CT downgraded the staging of a breast cancer patient and changed their treatment management - Jingjie Qin; Jingjing Zhao; Jinming Yu; Yuchun Wei (Precision Radiation Oncology)
Abstract A 47‐year‐old woman underwent [18F]‐FDG and [18F]‐NOTA‐FAPI‐04 PET/CT to assess the staging of suspected axillary lymph node enlargement following breast‐conserving surgery. The imaging with these two PET agents revealed starkly contrasting results. Significant [18F]‐FDG uptake in the right axillary fossa, intrathoracic muscles, and clavicle lymph nodes led nuclear medicine physicians to suspect metastasis. However, no uptake of [18F]‐NOTA‐FAPI‐04 was observed. Subsequently, the patient underwent an ultrasound‐guided biopsy of the enlarged axillary lymph nodes, which pathologically confirmed the diagnosis as inflammation. After a multidisciplinary discussion, the patient received radiotherapy for the right breast and 2.15Gy/F×28F for the tumor bed. She was discharged following the completion of her radiotherapy. Accurate diagnosis and staging are pivotal in selecting the optimal clinical treatment for breast cancer patients. Notably, [18F]‐NOTA‐FAPI‐04 PET/CT downgraded this patient's staging, significantly influencing the treatment strategy.